The AIDA 1 km resolution crop-specific rainfed and irrigated areas and green and blue water demands for Italy - Nikolas Galli; Harsh Nanesha; Arianna Tolazzi; Davide Danilo Chiarelli; Maria Cristina Rulli (Scientific Data)
Abstract Climate and global changes alter natural resources demand and availability for meeting societal needs. Agricultural water use remains a priority, as agriculture remains the first freshwater consumer. Accurate mapping of irrigated and rainfed crops is crucial in agro-hydrological modelling for water management and policy. Taking Italy as prominent case, we present AIDA (Agricultural Irrigation Demand Analyzer), a set of high-resolution crop-specific maps of rainfed and irrigated areas and water demands. We combine very-high resolution crop-specific landcover datasets with cropland ground data and irrigation intensity maps to derive 1km-resolution maps for rainfed and irrigated crops in the entire Italian territory. A dynamic, spatially distributed agro-hydrological model with state-of-the-art inputs derives evapotranspirative demands partitioned into green water (from precipitation stored as soil moisture) and blue water (from irrigation). Our results have a linear correlation >75% and an error <20% w.r.t. subnational statistics in >80% of the areas. Despite limitations due to inputs, assumptions on hydrological processes and agricultural practices, AIDA complements existing hydrological models and land use datasets for Italy.